Application effect of diversified health-promoting models on rehabilitation exercises for cervical spondylotic myelopathy - Lin, Bi-Hua; Zhong, Gui-Qin; Meng, Xiao-Hong; Han, Hai-E; Hu, Xue-Qin; Lin, Jing-Jing; Zhong, Shi-Chai; Lin, Yan-Juan (Technology and health care, 2024)
BACKGROUND: With improving living standards, the incidence of cervical spondylotic myelopathy (CSM) has become increasingly high. OBJECTIVE: The study aims to explore the effect of diversified health-promoting models on rehabilitation exercises in patients with CSM after an operation. METHOD: This was a randomized controlled trial, wherein 107 patients with CSM treated by neurosurgery were selected as the subjects. Of those, 52 patients in the control group adopted the conventional health-promoting model, while the remaining 55 patients in the intervention group adopted diversified health-promoting models. The effect of rehabilitation exercises in the two groups was evaluated according to the self-efficacy rehabilitation outcome scale, grip strength measurement of the affected limb, and Barthel index. RESULTS: At Day 3 post-operation and before discharge, the self-efficacy management of rehabilitation exercises in the intervention group was better than that of the control group ( P < 0.05). The grip strength measurement of the affected limb, Japanese Orthopedic Association score of the cervical vertebra, and Barthel index of the two groups at Day 3 post-operation were lower than before the intervention and were not statistically significant ( P > 0.05). However, these three items before discharge were improved when compared with those of before intervention and were statistically significant ( P < 0.05). CONCLUSION: Postoperative rehabilitation exercises guided by the diversified health-promoting models for patients with CSM can improve the patients’ self-efficacy management ability in rehabilitation exercises, help improve grip strength, and promote the recovery of cervical vertebra function, thereby improving the patients’ quality of life.